Microsatellite markers for the notothenioid fish Lepidonotothen nudifrons and two congeneric species. (December 2016) - Papetti, Chiara; Harms, Lars; Jürgens, Jutta; Sandersfeld, Tina; Koschnick, Nils; Windisch, Heidrun; Knust, Rainer; Pörtner, Hans-Otto; Lucassen, Magnus
Abstract Background Loss of genetic variability due to environmental changes, limitation of gene flow between pools of individuals or putative selective pressure at specific markers, were previously documented for Antarctic notothenioid fish species. However, so far no studies were performed for the Gaudy notothenLepidonotothen nudifrons . Starting from a species-specific spleen transcriptome library, we aimed at isolating polymorphic microsatellites (Type I; i.e. derived from coding sequences) suitable to quantify the genetic variability in this species, and additionally to assess the population genetic structure and demography in nototheniids. Results We selected 43, 269 transcripts resulting from a MiSeq sequencer run, out of which we developed 19 primer pairs for sequences containing microsatellite repeats. Sixteen loci were successfully amplified inL. nudifrons . Eleven microsatellites were polymorphic and allele numbers per locus ranged from 2 to 17. In addition, we amplified loci identified fromL.  nudifrons in two other congeneric species (L. squamifrons andL. larseni ). Thirteen loci were highly transferable to the two congeneric species. Differences in polymorphism among species were detected. Conclusions Starting from a transcriptome of a non-model organism, we were able to identify promising polymorphic nuclear markers that are easily transferable to other closely related species. These markers can be a key instrument to monitor the genetic structure of the threeLepidonotothen species if genotyped in larger population samples. When compared with anonymous loci isolated in other notothenioids, i.e. Type II (isolated from genomic libraries), they offer the possibility to test how the effects of occurring environmental change influence the population genetic structure in each species and subsequently the composition of the entire ecosystem.